Sex differences in undergraduates academic and career aspirations and attitude towards marriage and parenthood / Loh Ann Swee - Loh , Ann Swee (1980)
This study seeks to investigate sex differences in male and female undergraduates attitudes and aspirations in the areas of education, career and marriage/parenthood. A sample of 30 respondents were interviewed with the use of a structured interview-questionnaire. This was carried out during a christian champ held in Cameron Highlands in April/May 1979. The sample was divided into males (n=15) and females (n=15). Many western studies in the areas mentioned have already been carried out and it would be interesting to see how the western findings fit into the Malaysian schme of things. Most of the findings in this study actually do support the western studies. Analysis of the results shows that more men than women tend to have higher aspiration both in academic work as well as in their careers. Women are also both in academic work as well as in their careers. Women are also perceived to be less intelligent but more diligent than men. Both males and females consider the wife’s career to be less important than the husband’s and that the wife’s main concern should be in the family. Many of the views put forward were typically sex-stereotyped.